KAJIAN PENERAPAN KESEHATAN DAN KESELAMATAN KERJA (K3) DALAM PROSES BELAJAR MENGAJAR DI BENGKEL DAN LABORATORIUM POLITEKNIK NEGERI SRIWIJAYA - Indrayani INDRAYANI; Ika Sulianti (PILAR, 2014)
Aspect of Health Safety and Environment (K3) must be focused on education world, one of the place is Politeknik Negeri Sriwijaya (Polsri), a university located at Palembang that mainly focus on practice before theory. The practiced is done at workshop and laboratory. To prevent any accident, Health Safety and Environment (K3) application should be studied on teaching and learning process at workshop or laboratory of Polsri. Responses from correspondences was taken by questioners towards lectures, technicians, and students majoring Civil Engineering, Chemical Engineering and Mechanical Engineering, and later analyzed by Likert Scale.The grade results of Health Safety and Environment (K3) knowledge from lectures, technicians, students at workshop averaging on A and B range is lower than 50%. It shows that Health Safety and Environment (K3) knowledge must be increased especially on Engineering Major. The result of Health Safety and Environment (K3) equipments used by lectures or technicians is lower than 50% also during teaching and learninprocess, in the contrary Health Safety and Environment (K3) equipments used by students at workshop and laboratory is more than 50%. It is good if 100% always used by them to prevent sickness and accidentbecause of works. The result of Health Safety and Environment (K3) management application at workshopand laboratory is lower than 40% from lectures and technicians, and the result by students is lower than 50%. Students agree that Health Safety and Environment (K3) management already conducted at workshop or laboratory. Moreover, review and management of Health Safety and Environment (K3) at workshop and laboratory still need to be improved.